Characteristics of Fishermen Communities in The Coastal of East Balikpapan - Tiara Irawanti; Eko Budi Santoso; Haryo Sulistyarso (Institut Teknologi Sepuluh Nopember, 2015)
This study aims to identify the characteristics of fishermen communities in coastal areas of East Balikpapan. This type of research is descriptive method, with the technique of observation and questionnaire. This study use proportional sampling of Manggar and Manggar Baru village. The results showed that the fishermen community still using simple tools to catch fish, difficulties in obtaining capital, and fishes catches are sold directly to the retainer or to the market, so that fishermen are not getting the added value production. By knowing the characteristics of fishermen communities are expected to give a discourse in the development area so as to improve the welfare of fishermen in the area of research.